Uropygial gland size and composition varies according to experimentally modified microbiome in Great tits - Jacob, Staffan (BioMed Central, 2014)
BACKGROUND: Parasites exert important selective pressures on host life history traits. In birds, feathers are inhabited by numerous microorganisms, some of them being able to degrade feathers or lead to infections. Preening feathers with secretions of the uropygial gland has been found to act as an antimicrobial defence mechanism, expected to regulate feather microbial communities and thus limit feather abrasion and infections. Here, we used an experimental approach to test whether Great tits (Parus major) modify their investment in the uropygial gland in response to differences in environmental microorganisms. RESULTS: We found that males, but not females, modified the size of their gland when exposed to higher bacterial densities on feathers. We also identified 16 wax esters in the uropygial gland secretions. The relative abundance of some of these esters changed in males and females, while the relative abundance of others changed only in females when exposed to greater bacterial loads on feathers. CONCLUSION: Birds live in a bacterial world composed of commensal and pathogenic microorganisms. This study provides the first experimental evidence for modifications of investment in the defensive trait that is the uropygial gland in response to environmental microorganisms in a wild bird.